Pengaruh Pembiayaan Ijarah dan Pembiayan Qardh terhadap Return on Asset (ROA) pada Bank Pembiayaan Rakyat Syariah di Indonesia Periode 2017-2021 - Breghi, Willy; Cipta, Hendra; Amalia, Feby Ayu (JYRS: Journal of Youth Research and Studies, 2024)
Return On Assets is an indicator used to measure bank management's ability to obtain overall profits. The greater the Return On Assets of a bank, the greater the level of profit achieved by the bank. There are two factors that influence Return On Assets, namely Ijarah financing, Qardh financing. This research aims to analyze whether Return On Assets is influenced by Ijarah financing and Qardh financing. This research uses a quantitative method using secondary data with a sample of 60 sample data from all Sharia People's Financing Banks. The objects of research are Ijarah financing, Qardh financing, and Return On Assets at Sharia People's Financing Banks in Indonesia for the 2017-2021 period. Data collection techniques in this research used documentation techniques and literature study. The data analysis techniques used in this research are the classical assumption test, multiple linear regression test, and hypothesis testing. This research uses Eviews 12 Software. The results of this research show that the Ijarah variable partially has a negative and significant effect on Return On Assets which has a tcount value of - 2.235981> ttable value of 2.001717 and a significance value of 0.0293 <0.05 which shows that this variable has a negative and significant influence on the Return On Asset variable. The Qardh variable partially has no significant effect on Return On Assets which has a t-count value of the Qardh variable of -1.861409 >< ttable value of 2.001717 and a significance value of 0.0678 > 0.05 which shows that this variable has no effect on the Return On Asset variable. There is a significant simultaneous influence of the Ijarah and Qardh variables on Return On Assets at Sharia People's Financing Banks in Indonesia in 2017-2021. This shows that the simultaneous test results have an Fcount value of 11.49290> a Ftable value of 3.16 with a significance value of 0.000064